2011
DOI: 10.3892/mmr.2011.444
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits extracellular matrix synthesis by suppressing p38 and ERK1/2 pathways in TGF-β1-stimulated NRK-49F cells

Abstract: Abstract. emodin has been demonstrated to inhibit the fibrotic process in chronic renal disease, but its mechanisms have yet to be fully elucidated. This study was carried out to investigate the effects of emodin on extracellular matrix (ecM) synthesis in TGF-β1-stimulated NRK-49F cells. NRK-49F cells stimulated with TGF-β1 were incubated with various concentrations of emodin. ECM proteins, including collagen type III and fibronectin, were detected using ELISA. ERK1/2, p38 and JNK phosphorylation were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Our finding of emodin‐mediated inhibition of collagen type I through suppressing p38 MAPK phosphorylation, which correlates with its activation status, in activated HSCs is consistent with the observation of B. Zhu et al () in NRK‐49F cells. These results are not unexpected because activated HSCs and NRK‐49F cells share common characteristics of ECM production and vitamin A storage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of emodin‐mediated inhibition of collagen type I through suppressing p38 MAPK phosphorylation, which correlates with its activation status, in activated HSCs is consistent with the observation of B. Zhu et al () in NRK‐49F cells. These results are not unexpected because activated HSCs and NRK‐49F cells share common characteristics of ECM production and vitamin A storage.…”
Section: Discussionsupporting
confidence: 92%
“…Because MAPK is known to be noncanonical targets of TGFβ and emodin regulated p38 MAPK in NRK‐49F cells (Ding et al, ; B. Zhu et al, ), next, we tested if emodin suppresses p38 MAPK activity in activated HSCs. The data from the transcription factor activation assay presented in Figure a indicate that emodin robustiously inhibited MAPK‐induced transcription factors, including ATF‐2, signal transducer and activator of transcription 1, and myocyte enhancer factor 2 DNA binding activity in LX‐2 cells whereas DNA binding activity of c‐Jun and c‐Myc was unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, rhubarb also contains several glycosides, catechins, gallic acid, and cinnamic acid, together with small amounts of tannins . Emodin and rhein exert an anti-inflammatory effect through blocking of MAPK and PI3K pathway signaling Zhu et al, 2011) and inhibition of the activation of NF-κB and iNOS expression (Li et al, 2005). For quality control and clinical use of rhubarb, it will be important to determine whether other rhubarb components exhibit anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that Astragalus mongholicus and salvia miltiorrhiza protect renal function in rats with acute or chronic renal failure (Huang et al, 2007;Ngai et al, 2005). Rhubarb and its derived components inhibit renal fibrosis and inflammation to repress the deterioration of renal function (Chan et al, 2003;Hu et al, 2009;Peng et al, 2005;Wang et al, 2007Wang et al, , 2009Zhu et al, 2011). Radix salviae miltiorrhizae and its derived compounds alkanic acid have renal protective effects in ischemic kidney (Shen, 1988) or ischemia/reperfusion-induced renal injury (Kang et al, 2004).…”
Section: Discussionmentioning
confidence: 95%